E-clean house apps for Kampar residential - Lim, Ming Xuan (2024)
In this project, the e-clean House Apps for Kampar Residential mobile applications are developed to help people that don’t have time to clean their house without age limit and unable to clean their house conveniently and effectively. This mobile application is helping them to be able to book for maid to do their house chores as they are more professional compared to us. Besides that, there are three issues which are lack of loyalty programs, service is fixed and can’t be alter, and limited feedback and review mechanism. For the first issue, the application is lack of loyalty programs as loyalty programs is one of the best methods to keep user loyal. Therefore, one of the objectives is to provide users with a loyalty program. User can use this cleaning apps to exchange prize with the point gained from the loyalty program every time a transaction is done. By having this function, it can gain users trust and their loyalty as everyone like free gifts. Furthermore, the second issue is the service is fixed and can’t be alter. Some users prefer to have their house clean twice a month and some of them may prefer to clean one of their rooms and not the whole house, but most of the application services are fixed and can’t be change. This means that no matter the number of rooms that need to be cleaned, the price is already fixed, so users can’t choose the thing that they only want to clean. Thus, to solve this problem, we can provide more flexibility choice for the cleaning service. Hence, user has more flexibility in selecting the service they require and not the whole package. Other than that, user can also choose for their house type such as condominium, terrace, bungalow and other as well as the number of bedrooms and bathrooms. This will enhance the customer satisfaction as they only need to pay as they require. Moreover, the third issue is lack of dashboard for administration. Without a proper dashboard, it is hard to track accurate information about the sales. The dashboard come in three different graph that is the total sales graph, cleaner graph and cleaning type graph. The total sales graph will illustrate the total sales. The cleaner graph will illustrate the sales that have done by the cleaner. Finally, the cleaning type graph will illustrate the sales that have profit by which cleaning type. User can set the date based on their needs. For example, monthly, quarterly, half year, and yearly. Therefore, by fully utilizing the dashboard, we can maximize the efficiency of a good decision making.